Faktor-Faktor Yang Mempengaruhi Ibu Dalam Melakukan Inisiasi Menyusu Dini (IMD) Di Provinsi Maluku Utara Berdasarkan Analisis Data Riskesdas Tahun 2018 - Muhdar, Kusrini; Antaria, Abdullah; Upe, Al Asyary (Jurnal Kesehatan Rajawali, 2023)
Factors Influencing Mothers in Initiating Early Breastfeeding in North Maluku Province Based on 2018 Riskesdas Data Analysis. Thesis, Public Health Study Program. Muhammadiyah University Postgraduate School Prof. Dr HAMKA. 2019. The aim is to analyze the factors that influence mothers in initiating early breastfeeding based on the 2018 Riskesdas data analysis. The method used is a quantitative method. The research design uses a cross-sectional approach. The data used was secondary data from the 2018 Riskesdas. This study's population were mothers with babies and children aged 0-24 months in the 2018 Riskesdas census block, a total of 458. Data analysis used univariate analysis, bivariate analysis and multivariate analysis. The results showed that two variables had a p-value <α=0.05. Namely, the variable type of delivery had a p-value of 0.009 <α=0.05, with an OR value of 3.234. The place of delivery variable has a p-value of 0.014 <α=0.05, with an OR value of 2.347, while variables that have a p-value >α=0.05 or our mother's age, mother's educational level, mother's employment status, parity, birth attendant, the condition of the mother and the state of the baby. Health workers should be more intensive in initiating early breastfeeding according to the procedure for postpartum mothers, both vaginal and abdominal deliveries. For pregnant women to give birth at a health service facility in the local area.